Nonlinear association between neutrophil-to-lymphocyte ratio and asthma in children and adolescents in the United States: a cross-sectional study - Chuhan Cheng; Liyan Zhang (Clinical and Experimental Pediatrics, 2025)
Background The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation associated with various diseases including respiratory conditions. However, the relationship between NLR and asthma in the pediatric population remains underexplored. Purpose This study aimed to explore the association between NLR and asthma in children and adolescents and assess its potential role as a predictive biomarker for pediatric asthma. Methods We retrospectively analyzed the medical records of 12,974 children and adolescents from the National Health and Nutrition Examination Survey in 2011–2020. NLR was defined as the ratio of NLR counts. Asthma was diagnosed using a structured questionnaire. Multivariate logistic regression models were used to evaluate the association between NLR and asthma. A restricted cubic spline was used to explore nonlinear relationships, and a threshold analysis was conducted to identify potential cutoff values for the NLR. Results A total of 12,974 children and adolescents were included (male: 6,686 [51.5%]; mean [interquartile range] age, 10 [5.0–14.0 years]). After the adjustment for confounders, participants with the highest versus lowest NLR exhibited a significantly elevated risk of asthma (odds ratio [OR], 1.39; 95% confidence interval [CI], 1.13–1.71). Additionally, a multivariate restricted cubic spline analysis revealed a nonlinear relationship between NLR and asthma (P=0.023). A threshold analysis revealed that an NLR<2.23 was significantly associated with an increased risk of asthma (OR, 1.23; 95% CI, 1.05–1.45), while an NLR≥2.23 showed no significant association. A subgroup analysis revealed no interactive role of NLR and asthma. Conclusion Our findings indicate a nonlinear saturation-effect relationship between NLR and asthma in children and adolescents.